2001
DOI: 10.2519/jospt.2001.31.10.588
|View full text |Cite
|
Sign up to set email alerts
|

Hop Tests as Predictors of Dynamic Knee Stability

Abstract: Single leg hop tests are commonly used as physical performance measures of function and are also commonly used to evaluate progress in knee rehabilitation programs, particularly for individuals recovering from anterior cruciate ligament injury or reconstructive surgery. While there is some evidence that hop tests may show promise as a predictive measure for identifying individuals who are at risk for recurrent dynamic instability, further work is needed to clearly define the role of hop test measurements for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
153
1
7

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(167 citation statements)
references
References 28 publications
(2 reference statements)
6
153
1
7
Order By: Relevance
“…All single legged hop tests were supervised by the same physical therapist (HM). The functional examination consists of four previously described and validated single legged hop tests [11,15,17,42]. The tests include (1) the single hop test, (2) the triple hop test, (3) the triple crossover hop test, and (4) the six meter timed hop test.…”
Section: Performance Based Functional Hop Testsmentioning
confidence: 99%
“…All single legged hop tests were supervised by the same physical therapist (HM). The functional examination consists of four previously described and validated single legged hop tests [11,15,17,42]. The tests include (1) the single hop test, (2) the triple hop test, (3) the triple crossover hop test, and (4) the six meter timed hop test.…”
Section: Performance Based Functional Hop Testsmentioning
confidence: 99%
“…A huge variety of hop test procedures have been described [6,9,10,11,12,13] including vertical jump tests, timed hop and single leg hop tests for distance. Clinicians have used single leg hop tests to assess their patients' lower extremity muscular strength and ability to perform tasks that challenge knee stability [14]. These tests are also commonly used to evaluate progress in knee rehabilitation programs [14] or as an objective tool to evaluate a patient's total leg function [7].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 The uninjured limb (UL) is used as a reference, and the goal of rehabilitation is to increase side-to-side symmetry. 6,[8][9][10] The isokinetic test helps to quantify muscular recovery by measuring peak muscle torque of the extensor and flexor muscles of the knee joint. Some authors 1,11 have shown deficits in the quadriceps and hamstrings muscles after ACL reconstruction.…”
mentioning
confidence: 99%